Analisis Penerapan Akuntansi Manajemen Terhadap Kinerja Keuangan PT. RRK (Jurnal Kendali Akuntansi, 2023)
The purpose of this research is to examine the output of management accounting where managers of each division will make decisions in the future to evaluate the company's financial performance in PT. RRK . Research data is primary data obtained from interviews with the finance & accounting division and direct observation at the company. The research method uses a qualitative descriptive method. Based on the results of the analysis obtained, namely the management of PT. RRK through the finance & accounting manager has implemented management accounting in its business activities by making decisions based on financial reporting both from raw material shopping activities, sales recap to accounts payable. However, in terms of evaluation, PT. RRK cannot be said to be maximized because the scope is only as far as the financial perspective which should also be able to cover other perspectives if the evaluation system uses BSC (Balanced Score Card).